2022
DOI: 10.1097/acm.0000000000004639
|View full text |Cite
|
Sign up to set email alerts
|

The Model Minority Myth, Data Aggregation, and the Role of Medical Schools in Combating Anti-Asian Sentiment

Abstract: The COVID-19 pandemic has resulted in an alarming increase in hate incidents directed toward Asian Americans and Pacific Islanders (AAPIs), including verbal harassment and physical assault, spurring the nationwide #StopAsianHate movement. This rise in anti-Asian sentiment is occurring at a critical time of racial reckoning across the United States, galvanized by the Black Lives Matter movement, and of medical student calls for the implementation of antiracist medical curricula. AAPIs are stereotyped by the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Despite the success of AAPIs in medicine, we must not overlook the tragic history of anti-Asian sentiment in the United States, from the Chinese Exclusion Act of 1882, to the WWII Japanese internment camps, to the anti-Asian hate crimes that have risen in recent years. 1 These moments have had a profound impact on AAPIs, with race events since the COVID-19 pandemic as a particular concern for AAPI well-being and safety.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the success of AAPIs in medicine, we must not overlook the tragic history of anti-Asian sentiment in the United States, from the Chinese Exclusion Act of 1882, to the WWII Japanese internment camps, to the anti-Asian hate crimes that have risen in recent years. 1 These moments have had a profound impact on AAPIs, with race events since the COVID-19 pandemic as a particular concern for AAPI well-being and safety.…”
Section: To the Editormentioning
confidence: 99%
“…As we celebrate Asian American and Pacific Islander Heritage Month (at the time of writing), we are compelled to address Liu and colleagues’ article by calling on medical schools across the nation to recognize the realities we face. 1 As 2 Asians in the United States, we repudiate the notion of an ethnic monolith deserving of hate by raising awareness of our distinct heritages and challenging the myth of the model minority, which assumes that all Asian American Pacific Islanders (AAPIs) are able to achieve high levels of success, because of their well-educated and hardworking nature. We are 2 AAPI physicians-in-training with unique backgrounds and experiences: Filipino-American and Hong Konger, Asian American and Asian Immigrant, native and non-native English speaker, united by this dialogue.…”
Section: To the Editormentioning
confidence: 99%
“…Another recent study reported that East Asians (Chinese) achieved lower rates of leadership positions in the United States compared with South Asians due to perceptions of low levels of assertiveness among East Asians, 13 highlighting the importance of leadership training, unconscious bias awareness, and, as recommended by Lee at al, 12 redefinition of leadership attributes. Medical education and training, as noted by Liu et al, 3 must take the lead in supporting the next generation of healers as they prepare to care for increasingly diverse populations. The Liaison Committee on Medical Education (LCME), for example, requires that students learn to “recognize and appropriately address gender and cultural biases in themselves, in others, and in the health care delivery process,” which aligns with the AAMC’s Tools for Assessing Cultural Competence Training.…”
Section: Leadership In Medical Educationmentioning
confidence: 99%
“…An overriding challenge, as noted by Liu et al, 3 has to do with data that are too often aggregated and therefore misleading, extrapolated, or simply absent. Inattention to accurate data has, for too long, fueled the “no data, no problem, no policy” cycle of misrepresentation and omission.…”
Section: Representative Datamentioning
confidence: 99%
See 1 more Smart Citation